Psychology of Health Biopsychosocial Approach - George Taukeni, Simon (IntechOpen, 2019)
Psychology of Health - Biopsychosocial Approach is based on the bio-psychosocial model of health, which aims to examine how biological, psychological, and social factors influence people's behavior regarding their health status. This book reflects the application of the bio-psychosocial model of health in many disciplines such as public health, psychology, psychiatric, mental health, community health, and nursing education. All the authors of this book have demonstrated how the bio-psychosocial model played an important role in addressing mental disease, tuberculosis, post-traumatic stress disorder, and obesity. This is an important book for students, academics, policy-makers, and community health practitioners.